Studi Provenance Batupasir Karbonatan Formasi Kerek Dengan Metode Point Counting Di Daerah Kandangan Kabupaten Semarang - L. Muh. Fathur Rizki; Nofrohu Retongga; Andika Gerardus Oratmangun; Abdurrahman Saputra; Atikah Zahidah; Diana Septiani Roos; Rohmad Bagus Abadi; Oan Marcello Lukas Watania (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2021)
Carbonate sandstone in the study area was found around rivers and hills in the study area. Provenance of sandstones in the research area of interest to be examined, because not known provenance the sandstone rock formations karbonatan Kerek especially in the research area. The purpose of this study was to determine the provenance of Kerek carbonated sandstones in the study area using themethod point counting. The methodology used for the analysis of Provenance in the study area is using petrographic incisions. The results of the analysis of provenance on the five samples of carbonated sandstones of the Kerek Formation in the study area obtained data in the form of: rock types including lithic arenite (Pettijohn, 1975), the climate of the source area is semiarid (Nelson, 2007), the source rock type is plutonic rock (Tartosa, et al, 1991). ) and its tectonic setting is in the magmatic arc transitional arc sub-zone (Dickinson and Suczek, 1979).